Analysis of the Effect of Variations in Feed Rate on the Wear of HSS End Mill Cutters in CNC Milling Processes Using the Finite Element Method - Muhammad Hisyam Rizqulloh; Mochamad Mas'ud (CV. AFDIFAL MAJU BERKAH, 2025)
This study investigates the effect of feed rate variations on the wear of High-Speed Steel (HSS) end mill cutters during the CNC milling of Aluminum 5052. The research addresses the challenge of optimizing tool life by exploring the complex interplay between feed rate, temperature, and wear. A quantitative approach was adopted, combining experimental tests with a Finite Element Method (FEM) simulation. The experiment used a fixed cutting depth of 1.5 mm and varied feed rates at 30, 40, and 50 mm/min. Data on temperature and tool wear were collected using an infrared thermometer and a digital microscope, respectively, while FEM simulations were performed using ANSYS to analyze thermal and mechanical stresses. The results showed that tool wear was not linearly proportional to temperature, with the highest wear occurring at 40 mm/min, despite lower temperatures. The FEM simulations successfully visualized critical zones of stress and deformation, confirming that tool performance is a function of both thermal and mechanical factors. In conclusion, optimizing feed rate is crucial for minimizing wear, and this integrated approach provides a robust framework for enhancing machining efficiency.